Antigenicity and immunogenicity of different morphological forms of Borrelia burgdorferi sensu lato spirochetes - Sloupenska, Kristyna; Koubkova, Barbora; Horak, Pavel; Dolezilkova, Jana; Hutyrova, Beata; Racansky, Mojmir; Miklusova, Martina; Mares, Jan; Raska, Milan; Krupka, Michal (Scientific reports, 2024)
Borrelia burgdorferi sensu lato is a species complex of pleomorphic spirochetes, including species that cause Lyme disease (LD) in humans. In addition to classic spiral forms, these bacteria are capable of creating morphological forms referred to as round bodies and aggregates. The subject of discussion is their possible contribution to the persistence of infection or post-infection symptoms in LD. This study investigates the immunological properties of these forms by monitoring reactivity with early (n = 30) and late stage (n = 30) LD patient sera and evaluating the immune response induced by vaccination of mice. In patient sera, we found a quantitative difference in reactivity with individual morphotypes, when aggregates were recognized most intensively, but the difference was statistically significant in only half of the tested strains. In post-vaccination mouse sera, we observed a statistically significant higher reactivity with antigens p83 and p25 (OspC) in mice vaccinated with aggregates compared to mice vaccinated with spiral forms. The importance of the particulate nature of the antigen for the induction of a Th1-directed response has also been demonstrated. In any of morphological forms, the possibility of inducing antibodies cross-reacting with human nuclear and myositis specific/associated autoantigens was not confirmed by vaccination of mice.
Keywords: myši; antigeny bakteriální; Borrelia burgdorferi komplex; Antigens, Bacterial; Borrelia burgdorferi; lymeská nemoc; Animals; lidé; Mice; Humans; Borrelia burgdorferi Group; zvířata; Lyme Disease